Spillover effects of economic complexity on the per capita GDP growth rates of Mexican states, 1993-2013 - Gómez-Zaldívar, Manuel; Fonseca, Felipe J.; Mosqueda, Marco T.; Gómez-Zaldívar, Fernando (Estudios de Economía, 2020)
The opening up of the Mexican economy completely transformed the growth dynamics of the per capita Gross Domestic Product (GDP) of the country’s various states, with a clear tendency towards growth being concentrated in specific regions. In this study, we quantify the indirect or spillover effect of economic complexity on growth based on the following two facts: i) economic complexity is an important factor in explaining GDP growth rates, and ii) there is a clear regional pattern in the states’ economic complexity, i.e., the economic complexity variable shows a positive spatial autocorrelation. Our results provide two insights: first, that the estimated positive spillover effect of complexity on growth is not negligible, particularly for states in the north of the country, whose own economic complexity is as important as that of their neighbors. In contrast, the spillover effect in southern states is negative. Being located next to states with low levels of economic complexity has a significant negative externality that almost overrides the positive effect of a state’s own level of complexity. Our findings lead us to conclude that spillover effects may have played a more important role in explaining the diverse pattern of growth between northern and southern Mexico than previously thought.